1999
DOI: 10.1007/bf02461074
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of negative air ions in acute stress in rats with different typological behavioral characteristics

Abstract: Negatively charged air ions are of interest of researchers and physicians as an effective means of prophylaxis and treatment of a wide range of diseases. Our previous studies showed that negatively charged air ions have normalizing effects on important physiological functions in rats subjected to prolonged chronic stress [3] and acute immobilization stress [4]. These studies used either long-lasting (three weeks) exposure to air ions during chronic induction of neurosis or pre-treatment (daily for one week) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The findings of other studies for which SMDs were not calculated included increased motor activity with either polarity of air ion exposure [ 56 ], no effect of positive or negative air ion exposure on spontaneous motor activity [ 57 ], reduced pain response to aversive stimulation following positive air ion exposure [ 58 ], reporting the same data as the authors’ previous studies [ 53 , 54 ] discussed above, no evidence for avoidance of high air ion exposure of either polarity [ 59 ], and prevention of an acute stress response by exposure of immobilized rats to negative air ions [ 60 ]. While some of the studies reported that air ions affect some measured aspects of rodent behavior, none of the tests employed were sufficiently similar in content or validity to standard tests used to screen for antidepressant activity to constitute a test for this specific type of response [ 61 ].…”
Section: Resultsmentioning
confidence: 82%
“…The findings of other studies for which SMDs were not calculated included increased motor activity with either polarity of air ion exposure [ 56 ], no effect of positive or negative air ion exposure on spontaneous motor activity [ 57 ], reduced pain response to aversive stimulation following positive air ion exposure [ 58 ], reporting the same data as the authors’ previous studies [ 53 , 54 ] discussed above, no evidence for avoidance of high air ion exposure of either polarity [ 59 ], and prevention of an acute stress response by exposure of immobilized rats to negative air ions [ 60 ]. While some of the studies reported that air ions affect some measured aspects of rodent behavior, none of the tests employed were sufficiently similar in content or validity to standard tests used to screen for antidepressant activity to constitute a test for this specific type of response [ 61 ].…”
Section: Resultsmentioning
confidence: 82%
“…Although the mechanisms involved in mediating such effects have remained obscure, our findings suggest a neural mechanism involved in induction of physiological response by NAI. Livanova et al (1999) reported that exposure to NAI could prevent the increase in BP associated with acute stress, i.e., immobilization of rats, and suggested that the normalizing effects of NAI in rats under stress is due to its anti-hypoxic effect. Ryushi et al (1998) found that diastolic BP and 5-HT level in plasma during recovery following moderate exercise were significantly lower in the presence of NAI than in the absence of it.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that exposure to NAI decreased heart rate (HR) and blood pressure (BP) in spontaneously hypertensive rats (Ju and Kubo 1997) and during and after exercise (Sovijarvi et al 1979;Ryushi et al 1998). Livanova et al (1999) also reported that NAI inhibited the increase in BP associated with acute stress. These findings suggest that NAI could be effective in inhibiting sympathetic nervous activity and activating parasympathetic nervous activity.…”
Section: Introductionmentioning
confidence: 94%
“…The charged matter gathers together and precipitates out of the air. In addition to eliminating harmful particulates from the air, negative ions also have a number of unique health benefits [7][8][9]. A growing number of people are using personal and home air filtration products that generate negative ions to charge and remove airborne particulate matter to create localized zones of improved air quality [10][11][12].…”
Section: Introductionmentioning
confidence: 99%